High plasma coenzyme Q10 concentration is correlated with good left ventricular performance after primary angioplasty in patients with acute myocardial infarction. Issue 31 (August 2016) - Huang, Ching-Hui; Kuo, Chen-Ling; Huang, Ching-Shan; Tseng, Wan-Min; Lian, Ie Bin; Chang, Chia-Chu; Liu, Chin-San
Abstract : Abstract: Exogenous administration of coenzyme Q10 (CoQ10) has been shown in experimental models to have a protective effect against ischemia–reperfusion injury. However, it is unclear whether follow-up plasma CoQ10 concentration is prognostic of left ventricular (LV) performance after primary balloon angioplasty in patients with acute ST segment elevation myocardial infarction (STEMI). We prospectively recruited 55 patients with STEMI who were treated with primary coronary balloon angioplasty. Plasma CoQ10 concentrations were measured before primary angioplasty (baseline) and 3 days, 7 days, and 1 month after STEMI using high-performance liquid chromatography. Echocardiography was performed at baseline and at 6-month follow-up. The control group comprised 54 healthy age- and sex-matched volunteers. Serial circulating CoQ10 concentrations significantly decreased with time in the STEMI group. The LV ejection fraction at 6-month follow-up positively correlated with the 1-month plasma CoQ10 tertile. Higher plasma CoQ10 concentrations at 1 month were associated with favorable LV remodeling and systolic function 6 months after STEMI. Multiple linear regression analysis showed that changes in CoQ10 concentrations at 1-month follow-up were predictive of LV systolic function 6 months after STEMI. Changes in CoQ10 concentrations correlated negatively with baseline oxidized low-density lipoprotein and fibrinogen concentrations and correlated positively with leukocyte mitochondrial copy number at baseline. Patients with STEMI who had higher plasma CoQ10 concentrations 1 month after primary angioplasty had better LV performance at 6-month follow-up. In addition, higher plasma CoQ10 concentration was associated with lower grade inflammatory and oxidative stress status. Therefore, plasma CoQ10 concentration may serve as a novel prognostic biomarker of LV systolic function after revascularization therapy for acute myocardial infarction.